2021
DOI: 10.1080/17461391.2021.1931463
|View full text |Cite
|
Sign up to set email alerts
|

A new energetics model for the assessment of the power‐duration relationship during over‐ground running

Abstract: We evaluated the reliability of an over-ground running three-minute all-out test (3MT) and compared this to traditional multiple-visit testing to determine the critical speed (CS) and distance > CS (D´). Using a novel energetics model during the 3MT, critical power (CP) and work > CP (W´) were also evaluated for reliability and compared to the multiple-visit tests. Overground running speed was measured using Global Positioning Systems during fixed-speed trials on a 400 m track to exhaustion, at four intensitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The present study observed that τD′ was not related to CS regardless of linear or nonlinear equations used. On the other hand, τW′ was previously related to D CP or CP in cycling, running, and handgrip exercises (Skiba et al, 2012;Broxterman et al, 2016;Vassallo et al, 2020). As previously mentioned, it is possible that no relationship was found because of the high within-subject variability of τD'.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The present study observed that τD′ was not related to CS regardless of linear or nonlinear equations used. On the other hand, τW′ was previously related to D CP or CP in cycling, running, and handgrip exercises (Skiba et al, 2012;Broxterman et al, 2016;Vassallo et al, 2020). As previously mentioned, it is possible that no relationship was found because of the high within-subject variability of τD'.…”
Section: Discussionmentioning
confidence: 90%
“…As previously mentioned, it is possible that no relationship was found because of the high within-subject variability of τD'. Also, the discrepancies between results might, to a large extent, be due to these studies employing recovery intensity based on different exercise domains (Skiba et al, 2012;Vassallo et al, 2020) or different contraction-relaxation cycles (Broxterman et al, 2016). In accordance, when performing a visual inspection in figures presented by Skiba et al (2012), Vassallo et al (2020, the relationships would likely have a worse or no fit if only one exercise domain were used for recovery intensity Training sessions with a work/relief ratio of 2:1 (A) and with a work/relief ratio of 4:1 (B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation